GAIN2 trial overall survival with intense versus tailored dose dense chemotherapy in early breast cancer - Möbus, Volker; Lück, Hans-Joachim; Ladda, Ekkehart; Klare, Peter; Engels, Knut; Schmidt, Marcus; Schneeweiss, Andreas; Grischke, Eva-Maria; Wachsmann, Grischa; Forstbauer, Helmut; Untch, Michael; Marmé, Frederik; et al. (npj Breast cancer, 2024)
GAIN-2 trial evaluated the optimal intense dose-dense (idd) strategy for high-risk early breast cancer. This study reports the secondary endpoints pathological complete response (pCR) and overall survival (OS). Patients (n = 2887) were randomized 1:1 between idd epirubicin, nab-paclitaxel, and cyclophosphamide (iddEnPC) versus leukocyte nadir-based tailored regimen of dose-dense EC and docetaxel (dtEC-dtD) as adjuvant therapy, with neoadjuvant therapy allowed after amendment. At median follow-up of 6.5 years (overall cohort) and 5.7 years (neoadjuvant cohort, N = 593), both regimens showed comparable 5-year OS rates (iddEnPC 90.8%, dtEC-dtD 90.0%, p = 0.320). In the neoadjuvant setting, iddEnPC yielded a higher pCR rate than dtEC-dtD (51.2% vs. 42.6%, p = 0.045). Patients achieving pCR had significantly improved 5-year iDFS (88.7% vs. 70.1%, HR 0.33, p < 0.001) and OS rates (93.9% vs. 83.1%, HR 0.32, p < 0.001), but OS outcomes were comparable regardless of pCR status. Thus, iddEnPC demonstrates superior pCR rates compared to dtEC-dtD, yet with comparable survival outcomes.
Gesehen am 07.02.2025